Improved anticancer effect of magnetite nanocomposite formulation of gallic acid (Fe3O4-PEG-GA) against lung, breast and colon cancer cells - Rosman, Raihana; Saifullah, Bullo; Maniam, Sandra; Dorniani, Dena; Hussein, Mohd Zobir; Fakurazi, Sharida (M D P I AG, 2018)
Lung cancer, breast cancer and colorectal cancer are the most prevalent fatal types of cancers globally. Gallic acid (3,4,5-trihydroxybenzoic acid) is a bioactive compound found in plants and foods, such as white tea, witch hazel and it has been reported to possess anticancer, antioxidant and anti-inflammatory properties. In this study we have redesigned our previously reported anticancer nanocomposite formulation with improved drug loading based on iron oxide magnetite nanoparticles coated with polyethylene glycol and loaded with anticancer drug gallic acid (Fe3O4-PEG-GA). The in vitro release profile and percentage drug loading were found to be better than our previously reported formulation. The anticancer activity of pure gallic acid (GA), empty carrier (Fe3O4-PEG) nanocarrier and of anticancer nanocomposite (Fe3O4-PEG-GA) were screened against human lung cancer cells (A549), human breast cancer cells (MCF-7), human colon cancer cells (HT-29) and normal fibroblast cells (3T3) after incubation of 24, 48 and 72 h using (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) MTT assay. The designed formulation (Fe3O4-PEG-GA) showed better anticancer activity than free gallic acid (GA). The results of the in vitro studies are highly encouraging to conduct the in vivo studies.